2011
DOI: 10.1007/978-3-642-24418-6_10
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Architectural Knowledge in Integrating Open Source Software

Abstract: Abstract. Open Source Software (OSS) is increasingly used in ComponentBased Software Development (CBSD) of large software systems. An important issue in CBSD is selection of suitable components. Various OSS selection methods have been proposed, but most of them do not consider the software architecture aspects of OSS products. The Software Architecture (SA) research community refers to a product's architectural information, such as design decisions and underlying rationale, and used architecture patterns, as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We identified three reasons for this: First, creators of SAD in OSS projects focus on specific use of SAD in OSS development, e.g., the architecture document elements which are directly helpful for the adaptation of OSS, and model, system, and mission description in SAD provides such help for developers to get a quick overview of the system, so that they can decide how to adapt it to different customer needs or deployment environments. Second, the OSS development provides limited incentives for developers to document SA design, and important knowledge on architecture design is mentally distributed over developers [43]. Third, some architecture document elements may not be included in SAD of OSS projects (e.g., concerns, stakeholders, and system-of-interest), but rather in other documents, such as user guide or system introduction.…”
Section: Relationship Between Architectural Languages Andmentioning
confidence: 99%
“…We identified three reasons for this: First, creators of SAD in OSS projects focus on specific use of SAD in OSS development, e.g., the architecture document elements which are directly helpful for the adaptation of OSS, and model, system, and mission description in SAD provides such help for developers to get a quick overview of the system, so that they can decide how to adapt it to different customer needs or deployment environments. Second, the OSS development provides limited incentives for developers to document SA design, and important knowledge on architecture design is mentally distributed over developers [43]. Third, some architecture document elements may not be included in SAD of OSS projects (e.g., concerns, stakeholders, and system-of-interest), but rather in other documents, such as user guide or system introduction.…”
Section: Relationship Between Architectural Languages Andmentioning
confidence: 99%
“…develop adapters and wrappers to facilitate integration of components. 'architectural model development' [10,24,30,31] architecture plays an important role in CBS development. An architectural model is developed to specify interaction of a CBS.…”
Section: Component Integration Challenges and Empirical Evaluationmentioning
confidence: 99%
“…Stol et al [30] presented an initial exploratory interview‐based study of software architects to investigate the importance of architectural knowledge in the integration of open source software components. The study showed that system integrators consider architectural knowledge valuable to assess the architectural fit of the component and understand how the component can be used for a CBS.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of such reasoning employ architecture centric approach. However, presently there are few well‐established architectural reasoning approaches and need extensive documentation . To overcome this issue, we use design decision that are in the form of relationships between the software structure; where a software structure embodies multiple design decisions.…”
Section: The Need For Reasoning Before Opportunistic Reusementioning
confidence: 99%